2017
DOI: 10.1002/ange.201704241
|View full text |Cite
|
Sign up to set email alerts
|

Proton Transport in the Outer‐Membrane Flavocytochrome Complex Limits the Rate of Extracellular Electron Transport

Abstract: The microbial transfer of electrons to extracellularly located solid compounds,t ermed extracellular electron transport (EET), is critical for microbial electrode catalysis. Although the components of the EET pathway in the outer membrane (OM) have been identified, the role of electron/ cation coupling in EET kinetics is poorly understood. We studied the dynamics of proton transport associated with EET in an OM flavocytochrome complex in Shewanella oneidensis MR-1. Using aw hole-cell electrochemical assay,as i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 35 publications
(20 reference statements)
0
13
0
Order By: Relevance
“…It is important to note that the model proposed here does not preclude counter-ion flow. Indeed, Okamoto et al (78) recently reported evidence for proton transport associated with EET in the S. oneidensis MtrC and OmcA multiheme cytochromes.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that the model proposed here does not preclude counter-ion flow. Indeed, Okamoto et al (78) recently reported evidence for proton transport associated with EET in the S. oneidensis MtrC and OmcA multiheme cytochromes.…”
Section: Discussionmentioning
confidence: 99%
“…[15,16] It is also known that electron transfer is usually coupled to proton transfer which causes acidification in the anodic biofilms and in the anolyte with deleterious consequences for the biofilm metabolism and stability. [3,17,18] The fundamental understanding of these processes that involve large proteins (>70 kDa) often with complex redox properties (with ≥10 heme centers in some multihemes cytochromes) is still in its infancy and precludes the optimization of microbial electrochemical technologies. In Gram-negative electroactive bacteria such as Shewanella, several redox proteins have pH-dependent potentials, [19] such as flavocytochrome c 3 (M r = 63.8 kDa) which is one of the most abundant proteins in the periplasm and the only functional fumarate reductase in this microorganism.…”
Section: Introductionmentioning
confidence: 99%
“…For confirmation of the rate limitation by the EET process, monitor the effect of adding shuttling electron mediators such as 100 µM anthraquinone-1-sulfonate ( α-AQS). See the section of Representative Results and reference 15…”
Section: Addition Of Deuterium Water To Measure the Kie On The Eet Prmentioning
confidence: 99%
“…The solid line in Figure 4a is the representative result for the microbial current change induced by the D 2 O addition. The addition of 1.0% (v/v) D 2 O sharply decreased the microbial current within 10 s, while almost no current decrease was observed by the addition of H 2 O (dotted line in Figure 4a) 15 . The same tendency was reproduced in at least four separate experiments.…”
mentioning
confidence: 94%
See 1 more Smart Citation